2013
DOI: 10.1177/0894845313483003
|View full text |Cite
|
Sign up to set email alerts
|

Feeling the Threat

Abstract: Social cognitive career theory (SCCT; Lent, Brown, & Hackett, 1994, 2000) holds that contextual barriers inhibit self-efficacy and goal choice intentions from points both near and far from the active career development situation. The current study examined the influence of one such proximal barrier, stereotype threat, on attainment of these outcomes among women considering careers in science. Participants were female undergraduate students (N = 439) enrolled in chemistry and physics laboratory classes. As pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(23 citation statements)
references
References 41 publications
3
17
0
Order By: Relevance
“…One direction for future research is stereotype threat, "a situation where one faces judgment based on societal stereotypes about one's group" [38] (p. 5) because it may depress the self-efficacy states of women in physics. Consistent with this study's findings, stereotype threat occurs for women in physics but not in chemistry [39][40][41]. Stereotype threat induces a stress response [42,43] that undermines learning [44] and performance [45,46], and higher stress correlates with lower self-efficacy [21].…”
Section: Discussionsupporting
confidence: 83%
“…One direction for future research is stereotype threat, "a situation where one faces judgment based on societal stereotypes about one's group" [38] (p. 5) because it may depress the self-efficacy states of women in physics. Consistent with this study's findings, stereotype threat occurs for women in physics but not in chemistry [39][40][41]. Stereotype threat induces a stress response [42,43] that undermines learning [44] and performance [45,46], and higher stress correlates with lower self-efficacy [21].…”
Section: Discussionsupporting
confidence: 83%
“…All five items used in the present study possessed good reliability (a = .86). Deemer, Thoman, Chase, and Smith (2014) documented evidence of the original three items' construct validity by demonstrating a positive correlation between stereotype threat and actual number of men in a classroom (i.e., women outnumbered by men).…”
Section: Methodsmentioning
confidence: 99%
“…Integrating this work on socio-cognitive career theory with theory on social identity processes at work, we argue that gender identity threat forms an important explanatory mechanism as to why male dominated work contexts impose a contextual barrier for female STEM graduates’ career confidence. Initial support among student samples showed that female STEM students’ experience of gender identity threat in male-dominated educational contexts lowered their self-efficacy (Deemer et al, 2014) and career motivation (see for review Thoman et al, 2013) in STEM. Thus, we hypothesize that:…”
Section: Theory and Hypothesesmentioning
confidence: 99%